Investors' perception towards Islamic Unit Trust in Malaysia / Abdul Halim Mohamed Ibrahim ... [et al.] - Mohamed Ibrahim, Abdul Halim; Mohd Rashid, Ahmad Husni; Ali, Rosalan; Abd Wahid, Zainora (Institute of Research, Development and Commercialization (IRDC), 2006)
The objective ofthe study is to determine the investors' perception towards Islamic unit trust in Malaysia. A cross tabulation analysis in terms of age, race and education was conducted based on 4283 samples throughout Malaysia on the basis of23 self-administered questionnaires. The results of the study revealed that the respondents perceive the principle of halal, reputation offund manager and high returns as the determining factors for their investment in Syariah unit trust. Generally, results ofthe study show that all ethnic groups in Malaysia still perceive insufficient information on Islamic unit trust as the key contributing factor that discourages them to invest. Specifically, the respondents who have higher education perceive better dissemination ofinformation as the key determiningfactorfor their investment in Islamic unit trusts. Therefore, the lack ofinformation on Islamic unit trust has encouraged the non-Syariah investors to opt for a better alternative investment that they believe has lower risks and higher returns.